Frequent intoxication and alcohol tolerance in adolescence: associations with psychiatric disorders in young adulthood. (17th January 2020) - Sarala, Marian; Miettunen, Jouko; Koskela, Jari; Mustonen, Antti; Rose, Richard J.; Hurtig, Tuula; Veijola, Juha; Niemelä, Solja
Abstract: Aims: To assess the associations of intoxication frequency and number of drinks needed to become intoxicated in mid‐adolescence with onset of psychiatric disorders in early adulthood. Design, Setting and Participants: Prospective cohort study in Northern Finland, with people from the Northern Finland Birth Cohort 1986 who self‐reported adolescent alcohol use: 6548 subjects (69.4% of the original sample). Data on alcohol use were collected using questionnaires at ages 15–16 years. Measurements: Outcomes were any non‐organic psychosis, mood disorder, anxiety disorder, any substance use disorder (SUD) and all the studied psychiatric disorders in early adulthood gathered from nation‐wide health care, pension and insurance registers. Number of drinks needed to become intoxicated was categorized into three classes: (1) no alcohol use or intoxication, and (2) low and (3) high alcohol tolerance (more than seven/nine drinks for females/males) groups. Similarly, intoxication frequency was divided into three classes: (1) never, (2) one to two times and (3) three or more times during the past 30 days. Information regarding gender, family type, other drug use, psychopathology using Youth Self‐Report (YSR) total score and parental psychiatric disorders were used as covariates. Findings: In the multivariable analyses, both low [odds ratio (OR) = 3.0, 95% confidence interval (CI) = 1.3–6.7, P ‐value = 0.009] and high (OR = 4.4, 95% CI = 1.8–11.1, P ‐value = 0.001) alcohol tolerance were associated with increased risk of SUD. More frequent intoxication was associated with increased frequency of SUD (OR = 3.9, 95% CI = 2.0–7.3, P ‐value < 0.001) and mood disorder (OR = 1.6, 95% CI = 1.1–2.3, P ‐value = 0.008). The latter was attenuated after adjusting with concurrent psychopathology (YSR) and other drug use. Conclusions: Both higher alcohol tolerance and frequent intoxication in adolescence appear to be associated with increased risk of future substance use disorder.